Factors Influencing Expression of Antixenosis in Soybean to Anticarsia gemmatalis and Spodoptera frugiperda (Lepidoptera: Noctuidae) - Boica Junior, Arlindo Leal [UNESP]; Sardinha De Souza, Bruno Henrique [UNESP]; Costa, Eduardo Neves; Ribeiro, Zulene Antonio [UNESP]; Stout, Michael Joseph (Oxford Univ Press Inc, 2015)
This study aimed to evaluate some factors that influence the expression of antixenosis in soybean genotypes against Anticarsia gemmatalis Hubner and Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae). Free-choice and no-choice feeding assays were performed with the resistant soybean genotype IAC 100 and the susceptible genotype BRSGO 8360 using Anticarsia gemmatalis and Spodoptera frugiperda larvae. The following factors that may affect expression of resistance were evaluated: one larva versus two larvae per leaf disc; use of larvae without prior feeding suspension versus larvae starved for 3 h prior to the assay; leaf discs versus entire leaflets; upper part versus lower part of the plant; and, vegetative versus reproductive growth stages. The level of resistance exhibited by the genotype IAC 100 was high enough to not be obscured by the effects of all factors assayed in the present study upon the feeding preference of Anticarsia gemmatalis and Spodoptera frugiperda larvae. However, our results demonstrate the importance of knowing the optimal conditions for conducting an assay for evaluating resistance of genotypes for specialist and generalist insect species. Utilization of two larvae of Anticarsia gemmatalis per leaf disc, not starved before the assays, with leaf discs from the upper part of plants at the reproductive growth stage provided better discrimination of differences in antixenosis expression in soybean genotypes. For Spodoptera frugiperda, use of one larva per leaf disc, not starved before the assays, with leaf discs from the lower part of plants at the reproductive growth stage gave more satisfactory results for feeding preference tests.
Keywords: fall armyworm; feeding non-preference; host plant resistance; research methodologies; velvetbean caterpillar